Correlation between Exclusive Breastfeeding and Nutritional Status of Children Aged 6-24 Months in the Service Area of Puskesmas Sadang Kebumen Regency - Andayani, Dadag Agustin; Wulan Margiana (Viva Medika, 2025)
Nutritional problems in children under five represent a complex and urgent global health issue, including in the area of Puskesmas Sadang, Kebumen Regency, where cases of underweight are most common despite an increase in exclusive breastfeeding rates. This study aims to examine the relationship between exclusive breastfeeding and the nutritional status of toddlers aged 6–24 months. The study used a quantitative approach with a cross-sectional study design involving 68 respondents selected from 386 mothers through proportional stratified random sampling. Data were collected in April 2025 from Posyandu in the Puskesmas Sadang area and analyzed using univariate and bivariate methods. Exclusive breastfeeding is the independent variable and toddlers nutritional status is the dependent variable. The results revealed that 80.9% of mothers provided exclusive breastfeeding, and 77.9% of toddlers had normal weight. Meanwhile, 17.7% were underweight or severely underweight, and 4.4% were at risk of being overweight. The Spearman correlation test showed a significant relationship between exclusive breastfeeding and the nutritional status of toddlers with a correlation coefficient score of r = 0.631 and p = 0.000 (p < 0.05).